Discovering signaling mechanisms governing metabolism and metabolic diseases with Drosophila. - Kim, S.K.; Tsao, D.D.; Suh, G.S.B.; Miguel-Aliaga, I. (Cell Metabolism, 2021)
There has been rapid growth in the use of Drosophila and other invertebrate systems to dissect mechanisms governing metabolism. New assays and approaches to physiology have aligned with superlative genetic tools in fruit flies to provide a powerful platform for posing new questions, or dissecting classical problems in metabolism and disease genetics. In multiple examples, these discoveries exploit experimental advantages as-yet unavailable in mammalian systems. Here, we illustrate how fly studies have addressed long-standing questions in three broad areas-inter-organ signaling through hormonal or neural mechanisms governing metabolism, intestinal interoception and feeding, and the cellular and signaling basis of sexually dimorphic metabolism and physiology-and how these findings relate to human (patho)physiology. The imaginative application of integrative physiology and related approaches in flies to questions in metabolism is expanding, and will be an engine of discovery, revealing paradigmatic features of metabolism underlying human diseases and physiological equipoise in health.